2019
DOI: 10.1177/2158244019865361
|View full text |Cite
|
Sign up to set email alerts
|

Corruption in Olympic Sports: Prevalence Estimations of Match Fixing Among German Squad Athletes

Abstract: Although match fixing threatens the integrity of competitions in sport, studies on the prevalence of match fixing are scarce. We measured the prevalence of competition manipulation by German elite athletes and the total percentage of these athletes who had been asked to participate in match fixing by using the randomized response technique. Approximately 8% of the athletes were asked to participate in match fixing, and approximately 7.5% were actually involved in competition manipulation during their careers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Despite the limitation, however, some parts of the results can provide several points of discussion given the common questions asked -such as the rates of approach for, involvement in, and awareness of match-fixing, as well as key instigators and motivations for involvement, etc. For instance, compared to the average rate of experienced approach from the six surveys (10.02%), our results show more or less the same rate of approach (10.12%), which may intimate that South Korean high-performance athletes are not particularly more vulnerable to the temptation of match-fixing [13,[16][17][18][19][20]. However, actual involvement of match-fixing amongst those approached varies from 1.2% to 7.47% (average 4.2%), while in our result, 4.5% (n=33) of respondents were involved in matchfixing [13,[16][17][18][19][20].…”
Section: Discussion: Incentives Weighed Against Sport Integritymentioning
confidence: 74%
See 2 more Smart Citations
“…Despite the limitation, however, some parts of the results can provide several points of discussion given the common questions asked -such as the rates of approach for, involvement in, and awareness of match-fixing, as well as key instigators and motivations for involvement, etc. For instance, compared to the average rate of experienced approach from the six surveys (10.02%), our results show more or less the same rate of approach (10.12%), which may intimate that South Korean high-performance athletes are not particularly more vulnerable to the temptation of match-fixing [13,[16][17][18][19][20]. However, actual involvement of match-fixing amongst those approached varies from 1.2% to 7.47% (average 4.2%), while in our result, 4.5% (n=33) of respondents were involved in matchfixing [13,[16][17][18][19][20].…”
Section: Discussion: Incentives Weighed Against Sport Integritymentioning
confidence: 74%
“…For instance, compared to the average rate of experienced approach from the six surveys (10.02%), our results show more or less the same rate of approach (10.12%), which may intimate that South Korean high-performance athletes are not particularly more vulnerable to the temptation of match-fixing [13,[16][17][18][19][20]. However, actual involvement of match-fixing amongst those approached varies from 1.2% to 7.47% (average 4.2%), while in our result, 4.5% (n=33) of respondents were involved in matchfixing [13,[16][17][18][19][20]. Perhaps the information about the awareness of others' match-fixing approach or involvement is the most unreliable given that it is about perception that can be based on rumours.…”
Section: Discussion: Incentives Weighed Against Sport Integritymentioning
confidence: 74%
See 1 more Smart Citation
“…FIFA, for instance, has the ability to punish states that attempt to hold their national football federation accountable to good governance principles by excluding them from qualifying for the next World Cup (Boudreaux et al, 2016). Additionally, international sport federations benefit from their social position and social power in society, which further complicates the task of accountability holders (Nelson & Cottrell, 2016). Moreover, in the Balkan countries, a recent study indicated that even the media is unable to hold the sport sector accountable, even though accountability holding is often regarded as one of its most important roles (Manoli & Janečić, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The opportunity structures for competition manipulation according to those sources were, however, highly similar to those mentioned in studies that did distinguish between both types. Namely, likely offenders are financially motivated (Carpenter, 2012;Doewes, 2020;Frenger et al, 2019;Gardiner et al, 2012;Huang et al, 2018;Trumpyte, 2016). Social ties, pressure, and duress (Carpenter, 2012;Gardiner et al, 2012;Kihl, 2019;Lee, 2017;, and conflicts of interests related to multi-club ownerships (Breuer, 2018) are also mentioned as contributing factors.…”
Section: Competition Manipulation (Non-specified)mentioning
confidence: 99%